ANALISIS PIUTANG TAK TERTAGIH BERDASARKAN UMUR PIUTANG PADA PT KAWASAN INDUSTRI GRESIK - Mustofah, Novia Trixie; Cahyadi, Nur (Kinerja, 2022)
This study aims to analyze bad debts based on the age of the receivables at PT Kawasan Industri Gresik. The company has two activities in sales activities, namely sales in cash or cash and credit or debt. If it is done in cash then the company does not have receivables from related parties, but if it is done on credit then the company has receivables that need to be billed. If the receivables are not paid, it will cause uncollectible receivables, and where this will affect the company's operational activities. This research method uses descriptive qualitative which aims to provide a representation of the condition of the company which is carried out by observation, documentation and interviews. From the data receivables are analyzed using the age of receivables to calculate the estimate of bad debts. The results showed that uncollectible accounts at PT Kawasan Industri Gresik decreased in the 2019 period to IDR 8,607,000,000, in 2020 to IDR 5,860,000,000 and in 2021 to IDR 3,878,000,000. This has been proven based on calculating the age of receivables using the method reserves in minimizing bad debts and reserves 5% for each aging account receivable that has been determined by the company.